KONTRIBUSI PENDAPATAN INDUSTRI RUMAHTANGGA MITRA NIAGADESA TERHADAP PENDAPATAN KELUARGA - Suminartika, Eti (Universitas Galuh, 2023)
Small scale industries income have decreased during the Covid-19 pandemic due to a decrease in its product demand. Improvement of the product and marketing system are needed to increase the income of industry. The purpose of this study is to analyze the contribution of household industry income of niagadesa's partner to family income. This research was conducted in Jagabaya village Mekarmukti district Garut regency West Java in October 2022. The research design is a qualitative design, the research method is a case study, the data used consists of primary and secondary data, primary data is obtained from interviews with household industry. Profit analysis used was in this study. The results showed: Before cooperating with Niagadesa, family income of household industry was Rp. 1,352,845 and it becomes Rp. 2,481,638 per month after cooperated, or an increase of 83 percent of family income. The household income contribution raised from 7% to 34% to family income. The increase of income was due to production technical guidance, packaging, and marketing, thus Niagadesa played a positive role to increase the income of his partner.